Individual- and area-level influence on suicide risk: a multilevel longitudinal study of Swedish schoolchildren. Issue 2 (24th April 2013) - Zammit, S.; Gunnell, D.; Lewis, G.; Leckie, G.; Dalman, C.; Allebeck, P.
Abstract : Background: Characteristics related to the areas where people live have been associated with suicide risk, although these might reflect aggregation into these communities of individuals with mental health or social problems. No studies have examined whether area characteristics during childhood are associated with subsequent suicide, or whether risk associated with individual characteristics varies according to childhood neighbourhood context. Method: We conducted a longitudinal study of 204 323 individuals born in Sweden in 1972 and 1977 with childhood data linked to suicide ( n  = 314; 0.15%) up to age 26–31 years. Multilevel modelling was used to examine: (i) whether school-, municipality- or county-level characteristics during childhood are associated with later suicide, independently of individual effects, and (ii) whether associations between individual characteristics and suicide vary according to school context (reflecting both peer group and neighbourhood effects). Results: Associations between suicide and most contextual measures, except for school-level gender composition, were explained by individual characteristics. There was some evidence of cross-level effects of individual- and school-level markers of ethnicity and deprivation on suicide risk, with qualitative interaction patterns. For example, having foreign-born parents increased the risk for individuals raised in areas where they were in a relative minority, but protected against suicide in areas where larger proportions of the population had foreign-born parents. Conclusions: Characteristics that define individuals as being different from most people in their local environment as they grow up may increase suicide risk. If robustly replicated, these findings have potentially important implications for understanding the aetiology of suicide and informing social policy.